The Influence of the Dormitory Program on the Formation of Environmental Care Character of Students of SMA Negeri Pintar Riau Province - Chelsa Artamevia; Haryono Haryono; Indra Primahardani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The research written in this article is motivated by the existence of a phenomenon which shows that some students at Smart Public High Schools in Riau Province do not yet have or lack the character of caring for the environment, for example their attitudes are not cleaning the bed, not turning off the lights after use, not participating in mutual cooperation and throwing away littering, while in the Smart State High School dormitory a dormitory program has been implemented which regulates all student activities for 24 hours in the dormitory. Therefore, the researcher is interested in conducting research with the aim of knowing whether there is an effect of the boarding program on the formation of the character of caring for the environment for students at SMA Negeri Pintar, Riau Province. The location of this research was carried out at the Smart State Senior High School in Riau Province which was based on a dormitory. The method used in this research is descriptive quantitative with data collection techniques, namely questionnaires (questionnaires), interviews and documentation. Based on the results of statistical calculations, Tcount (8.031) Ttable (2.017) means that Ha is accepted. Based on the results of the linear regression equation, the equation is Y = 2.286 + 0.911X meaning that if the hostel program (X) has increased by 1%, then the character of caring for the environment (Y) has increased by 0.911. So that it can be concluded from the results of the T test that there is an influence between variable X on variable Y, meaning that Ha is accepted, namely: there is an influence of the boarding program on the formation of the character of caring for the environment of students at SMA Negeri Pintar Riau Province.